Meade at Gettysburg : A Study in Command - Brown, Kent Masterson, 1949- (Book collections on Project MUSE., 2021)
"Although he took command of the Army of the Potomac only three days before the first shots were fired at Gettysburg, Union general George G. Meade guided his forces to victory in the Civil War's most pivotal battle. Commentators often dismiss Meade when discussing the great leaders of the Civil War. But in this long-anticipated book, Kent Masterson Brown draws on an expansive archive to reappraise Meade's leadership during the Battle of Gettysburg"--